Performance Evaluation of ns-3 Real-Time Emulation - Ottens, Martin; Deutschmann, Jörg; Hielscher, Kai-Steffen; German, Reinhard (IEEE Access, 2025)
With its real-time mode and tap-bridges, the network simulator ns-3 offers the possibility to integrate real applications or even hardware into a testbed in which ns-3 emulates the network topology. This eliminates the need to develop separate simulation models. However, there are several differences compared to a model-based discrete event simulation, where applications and network topology run together in the simulation process without real-time constraints. Using ns-3 to build an emulation environment makes it necessary to run in real-time mode, which results in considerable limitations with regard to the achievable throughput and the complexity of the simulated topology. This paper compares the performance that researchers can expect from pure model-based simulations and ns-3-based emulation environments. For this, we evaluate the impact of differently complex network topologies and applications on the simulator throughput in a minimal emulation setup. All measurements are compared with a pure model-based simulation setup. The performance of our setup is measured by the number of possible TCP and UDP flows. With complex network topologies and applications, only a few flows can be handled. In contrast, with simple topologies and applications, the measured throughput of our emulation setup is between 14 Mbps and 120 Mbps. We demonstrate that the achievable throughput additionally depends on ns-3 build profiles and CPU characteristics, highlighting, in particular, the impact of packet throughput as a limiting factor.
Keywords: Real-time systems; Network topology; Emulation; Topology; Performance evaluation; Throughput; Routing protocols; Computational modeling; Complexity theory; Codes

Proto2Testbed: Towards an Integrated Testbed for Evaluating End-to-End Security Protocols in Satellite Constellations - Ottens, Martin; Deutschmann, Jörg; Hielscher, Kai-Steffen; German, Reinhard (2025 12th Advanced Satellite Multimedia Systems Conference and the 18th Signal Processing for Space Communications Workshop (ASMS/SPSC), 2025)
There are many approaches to testbed systems in computer networks, but especially when evaluating or developing new security protocols and testing their behavior when used via satellite networks, many challenges remain that no existing system has fully addressed.With Proto2Testbed, we present an approach for a new testbed system that relies on isolated virtual machines. Once a specific testbed is defined, many steps of a typical testbed lifecycle, like testbed setup and experiment coordination, are fully automated. The testbed can be used in multiple ways; one example is the integration of a satellite mega-constellation simulation, thus turning the testbed system into a complete end-to-end emulation environment.Examples are used to demonstrate that Proto2Testbed can be used for various experiments in its current state. The design of future experiments is outlined, which will include a testbed for extensive evaluations of end-to-end security protocol
Keywords: Testbed; Satellite communications; Security protocols; Emulation; Virtualization

Seque: Lean and Energy-aware Data Management for IoT Gateways - Sixdenier, Pierre-Louis; Wildermann, Stefan; Ottens, Martin; Teich, Jürgen (IEEE International Conference on Edge Computing and Communications (EDGE), 2023)